One-step solution synthesis and formation mechanism of flower-like ZnO and its structural and optical characterization. Issue 9 (July 2016) - Wang, Yongqian; Ma, Qun; Jia, Hanxiang; Wang, Zhengshu
Abstract: The regular hierarchical flower-like ZnO nanostructures assembled by nanosheets were successfully synthesized by one-step solution route with citrate assistance at room temperature. It was demonstrated that the concentration of citrate and the molar ratio of Zn 2+ /OH − had strong effect on the formation of nanosheets and self-assembly flower-like nanostructures. A reasonable formation mechanism of the flower-like nanostructures was proposed. According to UV–vis spectrum, the flower-like ZnO nanostructures exhibited strong light absorption, and the value of band gap of the obtained ZnO was estimated to be 3.26 eV. Moreover, the room-temperature photoluminescence (PL) spectrum of the sample presented only a near-band edge emission at 382 nm.